Application of OSPF Network in Spanning Tree Protocol Method to Prevent Looping Routing - Roi Humisar Sianturi; Tengku Muhammad Diansyah; Imran Lubis (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2020)
Network is a basic thing that must exist in an agency or company, because the network can facilitate us in terms of data exchange and data transfer. In this study the application of the OSPF network to the Spanning Tree Protocol method to maintain Looping Routing using the Graphical Network Simulator 3 (GNS 3) simulator is expected to be the main objective in facilitating work completion, especially in terms of communication system data collection. With the help of Routing which serves to determine the route traveled by a packet that originates from a source node to the destination node on the network. Open shortest path first (OSPF) is one of the dynamic routing protocols that uses a link-state algorithm to build and calculate the shortest path to all known destinations. STP functions as a protocol for managing connections using the spanning tree algorithm.